PHYSICAL SELF AS OBJECT OF RESEARCH IN STRUCTURE OF THE SELF-ATTITUDE OF THE PERSONALITY AT YOUTHFUL AGE - M. A. Romanova; E. V. Mikhaylik (Acta Biomedica Scientifica, 2015)
This article viewed physical self in self-attitude of personality atyouthful age. Youthful age is presented in the article as the age where emotional distress in relation to his "I" is increasingly becoming a conscious character, and along with the cognitive self-perception are the significant correlates of behavior. Information referred to in article underlines the importance of focused work on the harmonization in self-attitude of personality within the framework of psychological and pedagogical support in youthful age. It also provides statistics (correlation analysis of parameters by Spearman rank correlation) that show the features of personality development atyouthful age.